Expression Pattern of Sulf1 and Sulf2 in Chicken Tissues and Characterization of Their Expression During Different Periods in Skeletal Muscle Satellite Cells - He,L (2020)
ABSTRACT Heparan sulfate proteoglycans (HSPGs) are present on the cell surface and in the extracellular matrix in all metazoans. HSPGs interact with growth factors and receptors through heparan sulfate (HS) chains. The sulfation pattern of heparan sulfate chains influences signaling events mediated by heparan sulfate proteoglycans located on the cell surface. SULF1 and SULF2 are two endo-sulfatases that can cleave specific 6-O-sulfate groups within the heparan chains. To determine their possible roles in tissues and satellite cells in vitro, their expression pattern was examined in tissues from 40-day-old chickens and in satellite cells from the breast muscles of 1-week-old and 2-week-old chickens using RT-PCR and immunocytochemistry analyses. The SULF1 and SULF2 transcripts were widely distributed in various tissues. Upon increasing culture times in chicken´s primary skeletal muscle satellite cells, SULF1 and SULF2 expression in 1-week-old chickens was significantly higher than in 2-week-old chickens, suggesting that sulfatases play a key role in satellite cell development. Therefore, our findings increase our knowledge of sulfatase expression diversity and provide a solid basis for further research concerning this molecular mechanism.